Twenty-Four–Hour Reocclusion After Successful Mechanical Thrombectomy: Associated Factors and Long-Term Prognosis. Issue 10 (October 2019) - Marto, João Pedro; Strambo, Davide; Hajdu, Steven D.; Eskandari, Ashraf; Nannoni, Stefania; Sirimarco, Gaia; Bartolini, Bruno; Puccinelli, Francesco; Maeder, Philippe; Saliou, Guillaume; Michel, Patrik
Abstract : Background and Purpose—: Early arterial recanalization is a strong determinant of prognosis in acute ischemic stroke. Nevertheless, reocclusion can occur after initial recanalization. We assessed associated factors and long-term prognosis of reocclusion after successful mechanical thrombectomy (MT). Methods—: From the prospectively constructed Acute Stroke Registry and Analysis of Lausanne cohort, we included consecutive patients with anterior and posterior circulation strokes treated by successful MT (modified treatment in cerebral infarction 2b-3) and with 24-hour vascular imaging available. Reocclusion at this time-point was defined as new intracranial occlusion within an arterial segment recanalized at the end of MT. Through multivariate logistic regression, we investigated associated factors and 3-months outcome. In a 4:1 matched-cohort, we also assessed the role of residual thrombus or stenosis on post-recanalization angiographic images as potential predictor of reocclusion. Results—: Among 473 patients with successful recanalization, 423 (89%) were included. Of these, 28 (6.6%) had 24-hour reocclusion. Preadmission statin therapy (aOR [adjusted odds ratio], 0.27; 95% CI, 0.08–0.94), intracranial internal carotid artery occlusion (aOR, 3.53; 95% CI, 1.50–8.32), number of passes (aOR, 1.31; 95% CI, 1.06–1.62), transient reocclusion during MT (aOR, 8.55; 95% CI, 2.14–34.09), and atherosclerotic cause (aOR, 3.14; 95% CI, 1.34–7.37) were independently associated with reocclusion. In the matched-cohort analysis, residual thrombus or stenosis was associated with reocclusion (aOR, 15.6; 95% CI, 4.6–52.8). Patients experiencing reocclusion had worse outcome (aOR, 5.0; 95% CI, 1.2–20.0). Conclusions—: Reocclusion within 24-hours of successful MT was independently associated with statin pretreatment, occlusion site, more complex procedures, atherosclerotic cause, and residual thrombus or stenosis after recanalization. Reocclusion impact on long-term outcome highlights the need to monitor and prevent this early complication. Abstract : Supplemental Digital Content is available in the text.